2018
DOI: 10.3389/fphys.2018.00379
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Chemosensory Protein Gene NlugCSP8 by RNAi Induces Declining Behavioral Responses of Nilaparvata lugens

Abstract: Chemosensory proteins (CSPs) play imperative functions in chemical and biochemical signaling of insects, as they distinguish and transfer ecological chemical indications to a sensory system in order to initiate behavioral responses. The brown planthopper (BPH), Nilaparvata lugens Stål (Hemiptera: Delphacidae), has emerged as the most destructive pest, causing serious damage to rice in extensive areas throughout Asia. Biotic characteristics like monophagy, dual wing forms, and annual long-distance migration imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 100 publications
7
29
1
4
Order By: Relevance
“…lugens to identify the defense responses of its host plant. In one of our previous studies, eicosane (Ki = 12.37 μ mol/L) moderately bound with NlugCSP8 (Waris et al ., ), while in this study, it exhibited relatively high binding affinity with NlugCSP10 (Ki = 4.36 μ mol/L). In addition, we confirmed that the rice volatile 2‐tridecanone, which is known to attract the BPH (Obata et al ., ), and can stimulate ecdysone 20‐monooxygenase activity in Spodoptera frugiperda (Yu, ) and retard the development of Helicoverpa armigera (Zhang et al ., ), also exhibited relatively moderate binding affinity to NlugCSP10 (Ki = 6.34 μ mol/L).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…lugens to identify the defense responses of its host plant. In one of our previous studies, eicosane (Ki = 12.37 μ mol/L) moderately bound with NlugCSP8 (Waris et al ., ), while in this study, it exhibited relatively high binding affinity with NlugCSP10 (Ki = 4.36 μ mol/L). In addition, we confirmed that the rice volatile 2‐tridecanone, which is known to attract the BPH (Obata et al ., ), and can stimulate ecdysone 20‐monooxygenase activity in Spodoptera frugiperda (Yu, ) and retard the development of Helicoverpa armigera (Zhang et al ., ), also exhibited relatively moderate binding affinity to NlugCSP10 (Ki = 6.34 μ mol/L).…”
Section: Discussioncontrasting
confidence: 45%
“…The specificity of each primer set was authenticated by the melt‐curve, in which there was only one single gene‐specific peak, and the linear standard curve was used to calculate the amplification efficiency (E‐value) by the equation E = 10 −1/slope . The qRT‐PCR reaction was conducted in 20 μ L mixture containing 10 μ L SYBR Green PCR Master Mix, 1 μ L cDNA template, 0.5 μ L of each primer (1 μ mol/L) and 8 μ L sterilized ultrapure water using the following qRT‐PCR conditions; one cycle of 95 °C for 3 min, followed by 40 cycles of 95 °C for 10 s and 57 °C for 30 s. β ‐actin (GenBank accession number: EU179846) was used as a reference gene to calculate the relative expression levels (Zhou et al ., ; Waris et al ., ). The data were analyzed using the 2normalΔnormalΔCT method (Livak & Schmittgen, ).…”
Section: Methodsmentioning
confidence: 97%
“… Kulmuni and Havukainen (2013) showed that 5-helical CSPs are the only highly conserved CSPs in Arthropoda and are likely involved in functions other than chemosensation, whereas the vastly divergent 6-helical CSPs carry out solely chemosensory functions. Evidence strongly suggests that CSPs might be involved in chemodetection, as are OBPs ( Waris et al, 2018 , 2020b ). In the honeybee, CSP3 specifically binds some components of brood pheromone ( Briand et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, piercing-sucking insects feed on phloem sap while ingesting very little plant tissue, so foliar application of dsRNA by spraying is not likely to trigger an effective RNAi response in them. Microinjection is an effective strategy for delivering dsRNA into many orders of insects, including BPH Zhu et al, 2017;Waris et al, 2018;Ge et al, 2019), but this approach is not a feasible strategy for achieving widespread crop protection in the field (Huvenne and Smagghe, 2010;Scott et al, 2013;Liu et al, 2019). Recently, Li et al (2015) suggested that soaking the root system in dsRNA could be used as a dsRNA-delivery strategy during crop irrigation, which is also suitable for BPH control.…”
Section: Discussionmentioning
confidence: 99%